Variable presentations of dengue fever with diagnostic dilemma: A case series - Somnath Maitra,; Koushik Ray,; Debes Pal,; Oendri Bhattacharyya, (Asian Journal of Medical Sciences, 2024)
Dengue is a viral fever in humans which is caused by 4 serotypes of the flavivirus. It is spread by the bite of the infected Aedes mosquitoes. The acute febrile illness is often associated with multisystem involvement with complications. The case series presented here depicts atypical manifestations of dengue which may present with hypoplastic anemia, hepatitis, pancreatitis, and encephalopathy. The cases were diagnosed based on history of dengue with subsequent persistence of pancytopenia, presence of hepatitis, pancreatitis, and encephalopathy with serological evidence of dengue and after ruling out other possible etiologies supported by laboratory evidence of investigations. The bone marrow revealed pancytopenia with hypocellular marrow causing hypoplastic anemia, transaminitis and rise of lipase and amylase with symptoms diagnosed hepatitis, pancreatitis, and finally impairment of consciousness with electroencephalogram proved encephalopathy. The importance of the case series lies in the fact that atypical manifestations may occur in dengue patients challenging the physicians and early detection may avoid unnecessary treatment and complications.